QiDiTangShen granules alleviates diabetic nephropathy podocyte injury: A network pharmacology study and experimental validation in vivo and vitro - Fei Gao; Ying Zhou; Borui Yu; Huidi Xie; Yang Shi; Xianhui Zhang; Hongfang Liu (Heliyon, 2024)
Background: QiDiTangShen granules (QDTS), a traditional Chinese medicine (TCM) compound prescription, have remarkable efficacy in diabetic nephropathy (DN) patients, and their pharmacological mechanism needs further exploration. Methods: According to the active ingredients and targets of the QDTS in the TCMSP database, the network pharmacology of QDTS was investigated. The potential active ingredients were chosen based on the oral bioavailability and the drug similarity index. At the same time, targets for DN-related disease were obtained from GeneCards, OMIM, PharmGKB, TTD, and DrugBank. The TCM-component-target network and the protein-protein interaction (PPI) network were constructed with the Cytoscape and STRING platforms, respectively, and then the core targets of DN were selected with CytoNCA. GO and KEGG enrichment analysis using R software. Molecular docking to identify the core targets of QDTS for DN. In vivo, db/db mice were treated as DN models, and the urine microalbuminuria, the pathological changes in the kidney and the protein expression levels of p-PI3K, p-Akt, JUN, nephrin and synaptopodin were detected by immunohistochemistry, immunofluorescence method and Western blotting. After QDTS was used in vitro, the protein expression of mouse podocyte clone-5 (MPC5) cells was detected by immunohistochemistry, immunofluorescence and Western blot. Results: Through network pharmacology analysis, 153 potential targets for DN in QDTS were identified, 19 of which were significant. The KEGG enrichment analysis indicated that QDTS might have therapeutic effects on IL-17, TNF, AGE-RAGE, PI3K-Akt, HIF-1, and EGFR through interfering with Akt1 and JUN. The main active ingredients in QDTS are quercetin, β-sitosterol, stigmasterol and kaempferol. Both in vivo and in vitro studies showed that QDTS could decrease the urine microalbuminuria and renal pathology of db/db mice, and alleviate podocyte injuries through the PI3K/Akt signaling pathway. Conclusion: Through network pharmacology, in vivo and in vitro experiments, QDTS has been shown to improve the urine microalbuminuria and renal pathology in DN, and to reduce podocyte damage via the PI3K/Akt pathway.